DOES THE ADVANCED GLYCATION END PRODUCTS FOOD INTAKE INFLUENCE MORTALITY IN DIALYSIS PATIENTS? - Trajcheska, Lada; Arsov, Stefan; Vidimliski, Pavlina Dzekova; Selim, Gjulsen; Busletik, Irena Rambabova; Sikole, Aleksandar (Journal of Morphological Sciences; Vol 1 No 2 (2018): JMS, 2018)
Introduction: Advanced glycation end products (AGEs) are considered as uremic toxins and contribute to cardiovascular complications in HD patients.Consumption of specific foods is associated with increased AGEs.In this study we investigated the AGE food consumption as a potential risk of mortality in dialysis patients. Methods: A study group of 150 dialysis patients were asked to fill in a 7-day diet questionnaire where from the data on protein, calorie and AGEs daily food intakes were extrapolated.Patients were followed for 36 months. Kaplan-Meier survival curves were applied to estimate difference in survival in patients with low(below median intake), or high (above median intake) of AGEs. The median CRP level was obtained for survival correction by inflammation. Results: The mean age of study participants was 55 years and 62% of them were men. The average amount of daily intake of AGEs was 9.4 Â±4.0 MU/24 hours. The average daily protein and calories intake were within current recommendations. The median level of daily AGEs intake was 8.9 MU/day.When patients were stratified by AGEs rich or poor diet and inflammatory state, no difference for survival was found in all groups. Patients with high inflammation did not differ in survival in relation to rich or poor AGEs diet (p=0.614). In patients with low CRP better survival had patients consuming more AGEs, but the difference was not statistically significant (p= 0.167). Conclusion: Inflammation strongly impacts survival of dialysis patients. Rich AGEs food diet was not found to be at risk of mortality. Traditional diet explains better outcomes in dialysis patients.